Accountability in Malaysian Islamic social enterprises (ISEs): Stakeholder versus management perspectives - Muhammad Iqmal Hisham Kamaruddin; Sofiah Md Auzair (Universiti Utara Malaysia Press, 2024)
Indexed by ERa